2022
DOI: 10.3390/ma15062290
|View full text |Cite
|
Sign up to set email alerts
|

Foundational Investigation on the Characterization of Porosity and Fiber Orientation Using XCT in Large-Scale Extrusion Additive Manufacturing

Abstract: The great potential of Extrusion Additive Manufacturing (EAM) for structural prototyping in the automotive industry is severely limited by the directional bias in the build direction. The layerwise fabrication leads to reduced mechanical properties at the layer-to-layer interface compared to the bulk of the strand. Especially for the often-used semi-crystalline thermoplastics, the mechanical properties strongly depend on the processing parameters, even more so if short fibers are used as fillers. Therefore, id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…In the LS-MEX process, the addition of carbon fibres not only improves the mechanical properties but also the processability [27]. The reduction in residual thermal stresses due to the use of carbon fibres enables the production of large components, as the fibres absorb the stresses generated during the process.…”
Section: Materials Polyamide 6 Reinforced With 40 Wt% Carbon Fibresmentioning
confidence: 99%
“…In the LS-MEX process, the addition of carbon fibres not only improves the mechanical properties but also the processability [27]. The reduction in residual thermal stresses due to the use of carbon fibres enables the production of large components, as the fibres absorb the stresses generated during the process.…”
Section: Materials Polyamide 6 Reinforced With 40 Wt% Carbon Fibresmentioning
confidence: 99%
“…Different studies have conducted investigations on porosity effects on the mechanical performance of AM-fabricated CFRP composites [5][6][7][8][9][10][11][12]. However, there are still limited investigations on the quantitative comparison of fabrication temperature-related porosity effects.…”
Section: Current Understanding Of Deposition Temperature-related Poro...mentioning
confidence: 99%
“…Layer height (LH) is another critical factor affecting the formation of voids, with conflicting reports presented in the literature. In some samples, increasing LH has been shown to reduce the number and size of the pores at the layer interfaces [17]. In other samples, increasing LH increased the number of pores and size of voids [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that higher substrate temperatures can reduce void volume. Conversely, lower processing temperatures can increase the number and size of voids [17]. Layer height (LH) is another critical factor affecting the formation of voids, with conflicting reports presented in the literature.…”
Section: Introductionmentioning
confidence: 99%